2010
DOI: 10.2164/jandrol.109.007773
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality of Male Idiopathic Infertile Smokers and Nonsmokers: An Ultrastructural Study

Abstract: This retrospective study was aimed at evaluating the effects of cigarette consumption on semen parameters in a group of men with idiopathic infertility. The semen quality of 2 groups of men with idiopathic infertility, smokers (n 5 118) and nonsmokers (n 5 153), were compared. Conventional semen analysis was performed and sperm morphology was assessed by transmission electron microscopy (TEM). TEM data were elaborated by means of a mathematical formula based on a Bayesian technique able to furnish a fertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…These fi ndings were very ing seminal cotinine as a measure of tobacco consumption. The present fi ndings agree with those of previous studies (1,3,(25)(26)(27)(28). On the contrary, some researches reported different results (29)(30)(31)(32).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These fi ndings were very ing seminal cotinine as a measure of tobacco consumption. The present fi ndings agree with those of previous studies (1,3,(25)(26)(27)(28). On the contrary, some researches reported different results (29)(30)(31)(32).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have examined the effects of cigarette smoking on male fertility and the results Different studies have assessed the relationship between smoking and semen quality ushave suggested a substantial negative impact on sperm production, motility and morphology (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the group of cryptorchid boys where the mother was heavily smoking during pregnancy had significantly increased risk of bilateral cryptorchidism (52%) compared with the group of boys where the mother did not smoke (20%) [89]. Men who are heavy smokers show significantly lower sperm concentration and fertility index [143]. Other lifestyle factors, such as obesity, seem also to be of importance.…”
Section: Pathogenic Aspectsmentioning
confidence: 95%
“…Collodel et al [37] assessed morphological changes using transmission electron microscopy in idiopathic infertile male smokers compared with nonsmokers. They concluded that semen parameters were not significantly affected by smoking in cases of idiopathic infertility.…”
Section: Discussionmentioning
confidence: 99%